2014
DOI: 10.7600/jpfsm.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of training and non-training physical activity to physical activity level in female athletes

Abstract: We compared the physical activity level (PAL) and training and non-training physical activity (PA) between rhythmic gymnasts and lacrosse players. In addition, we aimed to clarify the contribution of training and non-training PA to the PAL. Our study subjects were 11 female rhythmic gymnasts and 11 female lacrosse players. PAL was calculated from the total energy expenditure (TEE) as assessed by the doubly labeled water (DLW) method, and the resting metabolic rate (RMR) was measured using indirect calorimetry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(26 reference statements)
0
1
0
1
Order By: Relevance
“…Bir araştırmada, yaş ortalaması 19,6 olan 11 ritmik cimnastik sporcusunun TEH'si 2798±247, 11 hokey oyuncusunun ise 2901±280 olarak bulunmuştur. 27 Sekiz hafta SKT antrenmanı yapan egzersiz grubumuzda ise bu değer 2720±454 olarak belirlendi. Çalışan sedanter kadınlar üzerinde yapılan başka bir araştırmada ise TEH; 2552±581 olarak kaydedilmiştir.…”
Section: Gereç Ve Yöntemlerunclassified
“…Bir araştırmada, yaş ortalaması 19,6 olan 11 ritmik cimnastik sporcusunun TEH'si 2798±247, 11 hokey oyuncusunun ise 2901±280 olarak bulunmuştur. 27 Sekiz hafta SKT antrenmanı yapan egzersiz grubumuzda ise bu değer 2720±454 olarak belirlendi. Çalışan sedanter kadınlar üzerinde yapılan başka bir araştırmada ise TEH; 2552±581 olarak kaydedilmiştir.…”
Section: Gereç Ve Yöntemlerunclassified
“…In human and animal studies, accelerometry is validated against directly observed movement or against energy expenditure, both methods being regarded widely as “gold standards” for the validation of movement ( De Vries et al., 2009 ; Yam et al., 2011 ). In humans, has been shown that there is an influence of gender and age on physical activity ( Belcher et al., 2010 ; Troiano et al., 2008 ), as well as a contribution of training in athletes ( Yoshida et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%